Coronavirus Disease 2019: Exploring Media Portrayals of Public Sentiment on Funerals Using Linguistic Dimensions - Saraff, Sweta; Singh, Tushar; Biswal, Ramakrishna (Frontiers in Psychology, 2021)
Funerals are a reflective practice to bid farewell to the departed soul. Different religions, cultural traditions, rituals, and social beliefs guide how funeral practices take place. Family and friends gather together to support each other in times of grief. However, during the coronavirus pandemic, the way funerals are taking place is affected by the country's rules and region to avoid the spread of infection. The present study was conducted to explore the media portrayal of public sentiments over funerals. In particular, the present study tried to identify linguistic dimensions associated with lexical components of social processes, affective processes, fear and disgust. An exhaustive search of newspaper coverage of funeral and related articles were made for a specific corona period. After initial screening for the details and language used, a total of 46 newspaper articles on funerals during the coronavirus pandemic were finalized for the analysis. Linguistic Inquiry and Word Count (LIWC) software were used to determine the association between linguistic dimensions of function words and words related to social and affective processes, as presented in the newspaper articles. Sentiment Analysis and Cognition Engine (SEANCE) was applied for the analysis of sentiment, social cognition, and social order. Bayesian correlation analysis and regression revealed positive and significant associations between function words and affective processes, between pronouns and social processes, and between negative adjectives and psychological processes of fear and disgust. Also, significant negative associations were found between polarity nouns and psychological processes of fear and disgust and between polarity verbs and psychological processes of fear and disgust. Bayes Factor 10 provides strong evidence infavor of the study hypotheses. Media is influenced by the prevailing sentiments in society and reflects their perception of the current social order and beliefs. The findings provide a glimpse into the prevailing sentiment of society through the lens of media coverage. These understandings are expected to enhance our observations of how people express their sentiments over the loss of their loved ones and help mental health professionals develop their therapeutic protocols to treat the COVID-19 affected population.